2021
DOI: 10.1007/s10143-021-01704-0
|View full text |Cite
|
Sign up to set email alerts
|

Clipping versus coiling for aneurysmal subarachnoid hemorrhage: a systematic review and meta-analysis of prospective studies

Abstract: Neurosurgical clipping and endovascular coiling are both standard therapies to prevent rebleeding after aneurysmal subarachnoid hemorrhage (aSAH). However, controversy still exists about which is the optimal treatment. This meta-analysis aims to assess the effectiveness and safety of two treatments with high-quality evidence. Web of Science, Cochrane Library, EMBASE, Pubmed, Sinomed, China National Knowledge Infrastructure, and Wanfang Data databases were systematically searched on August 5, 2021. Randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Prior studies by Swope et al and Hong et al [8,25] found worse HA pain to be associated with vasospasm or DCI, while studies by Huckhagel et al and Glisic et al did not [11,26]; of note, these studies have different outcome measures (vasospasm vs DCI), time spans examined, and inclusion criteria when compared to our study, however from these studies and our own observations there does not appear to be a strong association between HA pain severity and occurrence of DCI. Concerning other clinical characteristics, we found that many previously evaluated risk factors for vasospasm applied to DCI in this cohort, speci cally there was increased prevalence of DCI in patients receiving clipping for their aneurysm treatment as opposed to coiling [27].…”
Section: Discussionmentioning
confidence: 67%
“…Prior studies by Swope et al and Hong et al [8,25] found worse HA pain to be associated with vasospasm or DCI, while studies by Huckhagel et al and Glisic et al did not [11,26]; of note, these studies have different outcome measures (vasospasm vs DCI), time spans examined, and inclusion criteria when compared to our study, however from these studies and our own observations there does not appear to be a strong association between HA pain severity and occurrence of DCI. Concerning other clinical characteristics, we found that many previously evaluated risk factors for vasospasm applied to DCI in this cohort, speci cally there was increased prevalence of DCI in patients receiving clipping for their aneurysm treatment as opposed to coiling [27].…”
Section: Discussionmentioning
confidence: 67%
“…In a recent systematic review, coiling showed a better clinical outcome at short- and long-term follow-up, although the rebleeding risk was lower if patients received clipping. Furthermore, there was no significant benefit of one treatment modality over the other in patients with a poor neurological condition at admission 53. This review challenges the ‘coiling first’ policy in many western countries due to the higher costs of endovascular treatment.…”
Section: Challenges and Future Prospectsmentioning
confidence: 86%
“…The risk of early rebleeding after therapy is known to be strongly associated with the extent of aneurysm occlusion according to the CARAT study [ 24 ]. Zhu et al [ 25 ] revealed that clipping increases the incidence of complete aneurysmal occlusion by 33% compared to coiling. A literature review of 26 reports showed that delayed aneurysm rupture after coiling of unruptured aneurysms occurs in most cases when there is a remaining portion of the aneurysm, although it is also possible in cases where there is a remaining portion of the neck [ 26 ].…”
Section: Discussionmentioning
confidence: 99%